Aplikasi Pencatatan Kredit Motor Yamaha Pada PT. Mega Auto Finance (MAF) Sidoarjo - Dimas Priambodo; Mochammad Arifin; Vivine Nurcahyawati (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Abstract: PT. Mega Auto Finance (MAF) is a leasing company that provides credit service to purchase Yamaha motorcycle. The process of the credit services includes the customer’s credit in the form of address, phone number and so on that can change at any time, the loan application, approval of the loan application and loan repayment installments that are used as loan payments report for determining the list of delinquent consumers will be given on the collector. The company needs to perform data management in order to avoid delays in the process of credit approval, credit arrears report creation and reduce the time in search of data.The process of loan application data management must be done quickly to build applications motor credit records. This application is expected to be able to manage consumer data that can change at any time and reduce time in the loan approval process and recording payment of installments to facilitate the making of payments report. The payment report will be tailored to customer data so that the company can provide customer data accurately and arrears on the collector. Applications that have been made can manage customer data pencatatn, motors, credit application, credit approval and credit payments and generate reports loan payments and credit arrears so as to assist the company in improving the service. Keywords: Credit Application, Application, Data Management